Web-based language learning and speaking anxiety - Bashori, Muzakki; van Hout, Roeland; Strik, Helmer; Cucchiarini, Catia (Computer assisted language learning, 2022)
Foreign Language Speaking Anxiety (FLSA) is known to negatively affect the performance of foreign language learners. Among the four language skills, speaking is the most anxiety-provoking skill. We investigated the presence of FLSA in Indonesian vocational high school students and we tested whether web-based language learning might help to reduce speaking anxiety, in particular when the facility in question is equipped with Automatic Speech Recognition (ASR). A mixed methods research was employed to investigate FLSA in 573 vocational high school students. A subset of them (n = 167) was selected to participate in two ASR-based web-experiments using www.iloveindonesia.my.id and NovoLearning. We additionally interviewed 11 of the students who participated in these web-experiments and five English teachers. The results showed that students indicated a moderate-to-serious level of FLSA, that they evaluated the learning websites positively, and believed that web-based language learning could alleviate their speaking anxiety. The interviews revealed that students felt less anxious when speaking in front of the ASR-based websites compared to speaking to peers or people. In order to evaluate the real effectiveness of ASR-based learning websites, future studies should investigate actual improvement of learners' speaking skills over a longer period of time.